The Influence of Intrinsic Motivation and Synergistic Extrinsic Motivators on Creativity and Innovation - Fischer, Carmen; Malycha, Charlotte P.; Schafmann, Ernestine (Frontiers in Psychology, 2019)
Despite the vast amount of research focusing on intrinsic and extrinsic motivation, the effects of extrinsic motivators on creativity and innovation have been scarcely investigated. Extrinsic factors can be seen as synergistic extrinsic motivators when they have a positive effect on the outcome. The present study investigates synergistic extrinsic motivators that organizations can use to foster creativity and innovation of their intrinsically motivated knowledge workers. The analysis is based on Amabile and Pratt’s dynamic componential model of creativity and innovation in organizations combined with elements from Ryan and Deci’s self-determination theory. The quantitative data stemmed from 90 knowledge workers of an international consulting company who participated in an online self-assessment. In exploratory factor analyses, extrinsic motivation items consolidated two factors “relational rewards” and “transactional rewards”, while creativity and innovation items resulted in a one-factor solution, called “creativity/ innovation performance”. The results of hierarchical regression analyses confirmed the widely found positive effects of intrinsic motivation on creative and innovative performance. Moreover, the results supported the hypothesis that the extrinsic motivator, relational rewards, moderated the relationship between intrinsic motivation and creativity/ innovation performance significantly and positively. The findings showed the higher the perceived probability of receiving relational rewards and the higher the intrinsic motivation, the greater the positive effect on creative/ innovative outcomes. At the same time, the results did not confirm the hypothesis, that the moderator transactional rewards had a statistically significant effect on the relationship between intrinsic motivation and creative/ innovative performance. Finally, the empirical evidence provided practical implications on how to stimulate the creativity/ innovation performance of knowledge workers within organizations.